Pengaruh digitalisasi pajak terhadap kepatuhan membayar dan melaporkan pajak PPh 21 - Marisa, Auria Revi (Maliki Interdisciplinary Journal, 2024)
In today's digital era, the Directorate General of Taxes (DGT) is aggressively encouraging digitalization in taxation. Tax digitalization is one form of service from the Directorate General of Taxes (DGT) which aims to increase efficiency and effectiveness in tax administration which is related to improving taxpayer compliance. Through the implementation of various electronic tax systems such as e-filling and e-billing which are used as a means of paying and reporting pph 21, it significantly improves taxpayer compliance. This is because the electronic tax system makes taxpayers feel easier and faster in making payments and reporting PPH 21 taxes, then can also reduce the risk of errors, and increase tax accountability and transparency. Although it has a positive influence on tax compliance, it also presents several challenges such as limited technological infrastructure in some regions and resistance to change from some taxpayers.